The River Runs Red! Is it a Miracle, Is it an Ecological Disaster? Ito Romo’s El Puente/The Bridge - Ibarraran-Bigalondo, Amaia (Atlantis. Journal of the Spanish Association for Anglo-American Studies, 2014)
The implementation of the NAFTA agreement in 1994 precipitated unrestrained industrial growth on the Mexican side of the us-Mexico border, massive overpopulation, and the subsequent militarization of the area. The maquiladoras which now comprise part of the “natural landscape” of the border zone, determine the lives and destinies of those who work in/for them, and have brought about the severe environmental degradation of the region. Ito Romo’s El Puente/The Bridge (2000), a “minor story of major environmental protest,” provides a resounding denunciation of this situation and gives voice to the polluted Rio Grande and the inhabitants of the maquiladora zone. The effective use of simple language, simple people, and simple facts and acts assembled around a bizarre event provides the novel with a very effective vindicatory tone, turning it into the voice of a dying society which is gradually being ravaged, in the name of progress, by the vast industrial machinery of the maquiladora industry.